Image Captioning menurut Scientific Revolution Kuhn dan Popper - Agus Nursikuwagus; Rinaldi Munir; Masayu Leylia Khodra (Jurnal Manajemen Informatika (JAMIKA), 2020)
Image captioning is one area in artificial intelligence that elaborates between computer vision and natural language processing. The focus on this process is an architecture neural network that includes many layers to solve the identification object on the image and give the caption. This architecture has a task to display the caption from object detection on one image. This paper explains about the connection between scientific revolution and image captioning. We have conducted the methodology by Kuhn's scientific revolution and relate to Popper's philosophy of science. The result of this paper is that an image captioning is truly science because many improvements from many researchers to find an effective method on the deep learning process. On the philosophy of science, if the phenomena can be falsified, then an image captioning is the science.